Design and analytical validation of a duplex PCR for Ehrlichia and Rickettsia detection in ticks - Pérez Pérez, Juan C.; Montoya Ruiz, Carolina; Arroyave Sierra, Esteban; Paternina, Luis E.; Rodas, Juan D. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Ehrlichia and Rickettsia are two major rickettsial genera transmitted by ticks that affect a number of wild and domestic animal species and human populations around the world. Objective: To design and validate a duplex PCR for Ehrlichia and Rickettsia in ticks. Methods: Assay validation included testing for sensitivity, specificity, reproducibility, and robustness of the PCR. The groEL and 23sr RNA genes were used for Ehrlichia and Rickettsia, respectively. Results: The limit of detection was one hundred gene copies per 50 μL of reaction for Ehrlichia spp, and one gene copy of Rickettsia per 50 μL of reaction. In general, the primers of the test only amplified in silico those bacterial agents for which they were originally designed, with the exception of the primers for Rickettsia that also amplified Methylocystis sp. The test was reproducible (intermediate precision) 96.7% of the times for both agents. The test was robust enough to tolerate concentration changes of all reagents with the exception of Taq DNA polymerase. Conclusions: The validation results indicated that this PCR is useful for detection in both bacterial genera and it is a good candidate for diagnostic validation.